Does US Monetary Policy Affect Stock Market Behaviour Under Extreme Market Conditions? Evidence from COVID-19 - Kilic, Erdem; Sönmezer, Sitki (International Journal of Economics and Financial Issues, 2025)
We examine the short-term impact of Federal Open Market Committee (FOMC) announcements on technology stocks behavior. Using a modified continuous-time simulation model, we analyze high-frequency data for nine representative stocks from July 2019 to January 2021, covering ten FOMC announcement dates and the outbreak of COVID-19. High-frequency data provides more insight than lower frequent data. These insights enabled us to analyze the volatilities with higher incisiveness. Our results show differences in price jump patterns between mega-cap and second-tier large-cap stocks, varying degrees of noise dominance, and the presence of Brownian motion. Specifically, FOMC announcements increase market volatility and impact stock prices in different ways. Mega-cap stocks that are already financially strong appear to be less sensitive to interest rate increases than their smaller counterparts that rely on external financing.